2022
DOI: 10.3390/cancers14153782
|View full text |Cite
|
Sign up to set email alerts
|

NXPH4 Promotes Gemcitabine Resistance in Bladder Cancer by Enhancing Reactive Oxygen Species and Glycolysis Activation through Modulating NDUFA4L2

Abstract: Bladder cancer is one of the most prevalent kinds of cancer worldwide, and resistance to gemcitabine is a major problem for patients. The pathogenesis of bladder cancer and mechanism of resistance to chemotherapy remain to be explored. Through bioinformatics analysis, we first found that NXPH4 was independently related to the prognosis of patients with bladder cancer. Through wound healing assays, transwell invasion assays, and plate clone formation assays, we found that NXPH4 promoted the proliferation, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Our identification of the hypermethylation of some endocrine related genes, neuroexophilin-4 ( nxph4 ) and thyroid hormone receptor interacting protein-12 ( trip12 ), is relevant to the emerging concept that ALS is a metabolic syndrome [ 45 , 47 , 48 , 49 ]. Nxph4 is a secreted neuropeptide-like glycoprotein and a positive regulator of glycolysis and mitochondrial complex I [ 105 ]. Trip12 has many functions, including DNA damage and repair, chromatin remodeling, and muscle fiber selective proteasomal degradation of the multifaceted transcription factor Sox-6 [ 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our identification of the hypermethylation of some endocrine related genes, neuroexophilin-4 ( nxph4 ) and thyroid hormone receptor interacting protein-12 ( trip12 ), is relevant to the emerging concept that ALS is a metabolic syndrome [ 45 , 47 , 48 , 49 ]. Nxph4 is a secreted neuropeptide-like glycoprotein and a positive regulator of glycolysis and mitochondrial complex I [ 105 ]. Trip12 has many functions, including DNA damage and repair, chromatin remodeling, and muscle fiber selective proteasomal degradation of the multifaceted transcription factor Sox-6 [ 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mitochondrial complex I inhibitor was identified to be overexpressed in colorectal cancer (CRC) tissues and that is associated with tumor progression and poor prognosis ( 35 ). A prior study showed that NXPH4 can enhance cancer cell proliferation and invasion by modulating NDUFA4L2 in bladder cancer ( 13 ). To the other co-expressed genes, the hydroxymethyltransferase 2 (SHMT2) was reported as key regulators in the serine metabolism pathway and is involved in colon cancer proliferation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia shapes the landscape of the TME that contributes to tumor plasticity and heterogeneity and promotes highly aggressive and metastatic phenotypes ( 50 ). A previous study also showed that NXPH4 expression can promote reactive oxygen species (ROS) and glycolysis activation through modulating NDUFA4L2 to enhance gemcitabine resistance in bladder cancer cells ( 13 ). Another recent study reported that knockdown of NXPH4 was shown to inhibit cell proliferation, migration, and glycolysis in CRC cells ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurexophilin4 (NXPH4) is a neuro synaptic secretory protein. It is an essential neuropeptide-like glycoprotein that belongs to the neurophilic rexophilin family [ 12 ]. NXPH4 promotes cancer cell proliferation, migration, and invasion and is vital in the tumor metastasis cascade [ 12 ].…”
Section: Introductionmentioning
confidence: 99%